2018
DOI: 10.1590/2177-6709.23.2.062-067.oar
|View full text |Cite
|
Sign up to set email alerts
|

Perception of facial profile attractiveness of a brown subject displaying different degrees of lip projection or retrusion, in the city of Salvador/Bahia

Abstract: Introduction: The attractiveness and facial aesthetics are commonly defined by the media in modern society and the number of patients seeking for changes in the facial appearance is progressively increasing. Augmented face convexity is believed to be non aesthetic and among the treatments available for its correction, the extraction of premolars followed by anterior teeth retraction produces a significant effect. However, it is questionable whether the procedure is reasonable in brown and black patients, since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The revolution in communication and social media has led to changes in the beauty perception among most social media users, especially young adults. 13 , 14 The results could be the lack of acceptance of mild malocclusions and seeking a Hollywood smile. Added to this is the increased knowledge and awareness of what changes in orthodontic treatment can accomplish.…”
Section: Discussionmentioning
confidence: 99%
“…The revolution in communication and social media has led to changes in the beauty perception among most social media users, especially young adults. 13 , 14 The results could be the lack of acceptance of mild malocclusions and seeking a Hollywood smile. Added to this is the increased knowledge and awareness of what changes in orthodontic treatment can accomplish.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted to evaluate the perception of facial aesthetics among orthodontists and black laypersons in the Brazilian Northeast, a reference region for this black population, 6 , 10 consisting mostly of non-white people 25 , who historically have a convex and bi-protrusion profile as the most common features among them. 26…”
Section: Discussionmentioning
confidence: 99%
“…This result was compatible with that of studies in which orthodontists and laypersons preferred a slightly convex or straight profile as the most pleasant for black persons, for both African-Americans 33 and Afro-Brazilians. 6 The profile selected represented a less convex pattern than the type that was considered normal for black individuals, suggesting that the objective of the treatment should consider the ethnic characteristics and the point of view of the patient being treated. 33 , 6 Hall et al 17 found a preference for increased convexity of the soft tissues for Afro-Americans, when compared with White-Americans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the facial expressions that arises more interest in people and composes the beauty of it is the smile. [1][2][3] Therefore, studies have been conducted in order to reach a desired set of common characteristics for an optimal aesthetic smile. This goal is without successful perspective, since culture and ethnicity, values on what is beautiful and ugly or right and wrong vary on different continents, being illusory the idea of reaching a common denominator on this aspect.…”
Section: Introductionmentioning
confidence: 99%